Boosting inhibition control process by knitting at school - Sonnier, Frederic; Lussiana, Emeline; Gueraud, Sabine (Frontiers in Psychology, 2023)
Across two experiments, the presented research explored the impact of a knitting bout on elementary school pupils’ inhibition abilities. They proposed an accurate measure of the pupils’ inhibition abilities through the use of a stop-signal paradigm. In order to take into account, the differentiation between cool and hot inhibitions abilities, the emotional content of the stimuli was manipulated across experiments. Neutral materials were used in Experiment 1 when emotionally charged materials were in Experiment 2. The findings of both experiments highlighted a beneficial impact of the knitting bout on children’s inhibition abilities. While the results of Experiment 1 showed an optimization of inhibition abilities for the knitting session group in comparison to the control group, Experiment 2 revealed a disappearance of the effect of the emotional content on these abilities as well. Proposals as to why EF could be sensitive to knitting practice are discussed.